Validation of washing treatments to reduce Escherichia coli O157:H7 and Escherichia coli surrogates, Salmonella spp., and Listeria monocytogenes populations on the surface of green leaf lettuce, tomatoes, and cantaloupes - Lopez Giron, Keyla Patricia (Kansas State University, 2015)
Produce such as tomatoes, lettuce, and cantaloupes have been associated repeatedly with food outbreaks connected to various Salmonella serovars, Listeria monocytogenes, and Escherichia coli O157:H7. The aim of this research was to validate washing solutions and techniques in reducing pathogens on produce surfaces. Lettuce (25 ± 0.3g) and tomatoes were inoculated with E. coli O157:H7 and Salmonella spp., respectively. Samples were treated with tap water (TW) or a chemical wash treatment (CWT; containing citric acid) for 30, 60, or 120 s. Reduction of E. coli O157:H7 and Salmonella spp. populations on the surface of leaf lettuce and tomatoes, respectively, were greater (P<0.05) for CWT (ca. 3.0 logs) than for TW (ca. 2.3- 2.5 logs). Cantaloupes were washed with TW, 9% vinegar solution, or a commercial antimicrobial for fruit and vegetables treatment (CAFVT; containing lactic acid) for 2 min using a washing system. Cantaloupes were cut into wedges or cubes and stored at 4ºC for aerobic plate counts (APC) on days 0, 1, 3, and 6. APC populations of cubed and wedged cantaloupes were different over time (P=0.00052); cantaloupes washed with 9% vinegar solution showed the lowest APC populations after day 1 and 3 of storage. Salmonella spp. or L. monocytogenes inoculated cantaloupes were washed with CPW for 30, 60 or 120 s. Washing cantaloupes for 120 s with CPW showed greater (P<0.05) reductions of Salmonella spp. and L. monocytogenes populations (1.26 and 1.12 log₁₀ CFU/cm²) than TW (ca. 0.63 log₁₀ CFU/cm²) on cantaloupe surface. Lettuce leaves were inoculated with rifampicin-resistant E. coli surrogates and then washed with CAFVT, 5% vinegar solution or TW for 2 min with agitation (washing system) or without. Log reductions of CAFVT (2.25 log₁₀ CFU/g) were greater (P=0.0145) than those by tap water (1.34 log₁₀ CFU/g), but similar to 5% vinegar solution (2.09 log₁₀ CFU/g). Washing lettuce with continuous agitation achieved higher (P=0.0072) E. coli reductions (2.26 log₁₀ CFU/g) than without agitation (1.53 log₁₀ CFU/g). Overall, incorporation of wash solutions or agitation (washing system) in the washing process compared to TW alone reduced greater (P<0.05) APC, pathogens, or surrogates populations from lettuce, tomato, and cantaloupe surfaces.
Keywords: Escherichia coli; Salmonella; Listeria monocytogenes; Washing; Lettuce; Cantaloupe; Food Science (0359); Microbiology (0410)